Modelling biological pattern formation: The role of domain growth - Crampin, E; Maini, P (2001)
One of the central puzzles in developmental biology concerns the formation of spatio-temporal patterns during early embryogenesis. Although genes ultimately determine spatial structure and form, the study of genetics alone may not be sufficient to reveal the mechanisms which regulate production of patterns. These must arise due to interaction of underlying physical and chemical processes and, as such, are open to investigationvia mathematical modelling. Here, we review some of the most common mathematical models for biological pattern formation and present some recent results from studies that include domain growth.